THE CONTRACTION METHOD FOR RECURSIVE ALGORITMS. - RÖSLER, U.
RN THIS PAPER WE GIVE AN INTRODUCTION TO THE ANALYSIS OF ALGORITHMS BY THE CONTRACTION METHOD. BY MEANS OF THIS METHOD SEVERAL INTERESTING CLASSES OF RECURSIONS CAN BE ANALYZED AS PARTICULAR CASES OF OUR GENERAL FRAMEWORK.